Influence of different light sources on the production process of tomato in intensive photoculture - T. E. Kuleshova; O. R. Udalova; I. T. Balashova; L. M. Anikina; P. Yu. Kononchuk; G. V. Mirskaya; G. G. Panova (Овощи России)
Introduction. The development of ideas about the influence of the light environment - the radiation spectrum, intensity and duration of exposure, on the physiology of plants, serves as the basis for the creation of effective light sources for protected ground.Purpose. Comparative test of the influence of a light environment with different spectral composition on the productivity and quality of tomatoes in conditions of intensive photo culture.Methods. Investigations were made under controlled conditions of intensive photoculture when growing dwarf tomatoes of the variety Natasha selections of the “Federal Scientific Vegetable Center” on thin-layer soil analogs with the supply of a nutrient solution to the plant roots through a slit capillary in vegetative light installations developed at the ARI. The light sources were high-pressure sodium lamps and LED lamps SD1, SD2, and SD3 with different emission spectra. Results. Tomatoes of the Natasha variety, illuminated during development with HPS lamps, formed almost the same yield with an average fruit weight of 42.5 kg/m2 per layer per year. Natasha tomato grown under LED lamps showed a tendency to lower productivity by 29% under SD1 and by 8% under SD2 and higher by 19% under underSD3 compared to that under HPS lamps. A comparative assessment of the biochemical composition of tomato fruits indicates their high quality under all tested light sources.Conclusion. Cultivation of dwarf tomato varieties on thin-layer soil analogs showed the best results in terms of productivity with good quality plant products under LED lamps SD3 with a radiation spectrum close to sunlight.